Competency-based teacher education (CBTE): A training module to improve knowledge, attitude, and practices (KAP) of school teachers on learning disabilities in children - Ravichandran Rajesh; Zeanath Cariena Joseph (Journal of Family Medicine and Primary Care)
Introduction: Inclusive education is a new approach towards a system of educating children with disabilities and learning difficulties with that of normal ones within the same crown. Competency-based teacher education (CBTE) is a framework in which teachers demonstrate their learned knowledge, attitude, and skills in order to achieve specific predetermined “competencies” for a specific course or at a specific educational institution. Children with learning disabilities have significant impairment in reading, writing, and mathematics in spite of normal intelligence and sensory abilities. Aim: The aim of the study was to evaluate the effectiveness of competency-based teacher education (CBTE) training module on knowledge, attitude, and practices (KAP) of school teachers regarding learning disabilities in children. Materials and Methods: This was a Quasi experimental study carried out in the month of December 2020 using one group pretest and posttest design. Thirty-five school teachers from a private school were randomly selected as study subjects who were handling classes for primary school students at Kolar. School teachers who had prior exposure in special schools and who had already worked as a counsellor were excluded from this study. Data were collected via a self-administrated method with structured questionnaires consist of 150 items including sociodemographic profile, knowledge, attitude, and practice of teachers regarding learning disabilities in children; the data were analysed using descriptive and inferential statistics. Results: The findings indicated that mean post-test knowledge score was 35.89, attitude score was 170.66, and practice score was 69.60. The effectiveness of CBTE training module was found to be statistically significant at P < 0.05 in terms of mean scores enhancement in knowledge, attitude, and practices. In terms of correlation between knowledge, attitude, and practices of school teachers on learning disabilities in children, it was found that there was a highly positive correlation between attitude and practice with r = 0.884, and knowledge and practice with r = 0.905. Conclusion: The CBTE training module is an effective method in enhancing the knowledge, changing the desirable attitude, and developing good skills of school teachers regarding the identification and management of learning disabilities.